2019
DOI: 10.1093/ofid/ofz442
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella algae Infections in United States Naval Special Warfare Trainees

Abstract: Shewanella infections are uncommon in immunocompetent hosts. We report 6 cases of Shewanella algae infection in young, healthy Naval Special Warfare trainees in San Diego during 2 consecutive El Niño seasons, defining a unique population at risk and adding to the epidemiologic understanding of this potentially virulent organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Recent advances in the taxonomy and phylogenetic relatedness of Shewanella spp. supported the concept that most human infections were caused by S. algae [5,8].…”
Section: Introductionmentioning
confidence: 61%
“…Recent advances in the taxonomy and phylogenetic relatedness of Shewanella spp. supported the concept that most human infections were caused by S. algae [5,8].…”
Section: Introductionmentioning
confidence: 61%
“…However, prior reports of monomicrobial infection with S. algae have suggested the organism as causal in many cases, confirming its ability to cause disease [28][29][30]. Although infection in healthy hosts is uncommon, rare cases have been reported in individuals with no underlying diseases due to massive exposure to marine environment and seafood consumption [31][32][33]. The increased in S. algae virulence was attributed to its hemolytic activity, enzymatic activity, and biofilm formation [18,34,35].…”
Section: Introductionmentioning
confidence: 95%
“…23 Other studies have also reported variable resistance to ampicillin and cephalosporins in this species. 31 The antibiotic sensitivity report for our patient indicated that the strain of S. algae isolated from patient was susceptible to all β-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 70%